Transition Metal-Doped Layered Iron Vanadate (FeV3-xMxO9.2.6H2O, M = Co, Mn, Ni, and Zn) for Enhanced Energy Storage Properties - Mawuse Amedzo-Adore; Jeong In Han (Nanomaterials)
With its distinctive multiple electrochemical reaction, iron vanadate (FeV3O9.2.6H2O) is considered as a promising electrode material for energy storage. However, it has a relatively low practical specific capacitance. Therefore, using the low temperature sol–gel synthesis process, transition metal doping was used to enhance the electrochemical performance of layered structured FeV3O9.2.6H2O (FVO). According to this study, FVO doped with transition metals with larger interlayer spacing exhibited superior electrochemical performance than undoped FVO. The Mn-doped FVO electrode showed the highest specific capacitance and retention of 143 Fg−1 and 87%, respectively, while the undoped FVO showed 78 Fg−1 and 54%.